2019
DOI: 10.1523/jneurosci.3147-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Gain Analysis Reveals Encoding Deficiencies in Cortical Neurons That Recover from Hypoxia-Induced Spreading Depolarizations

Abstract: Cortical regions that are damaged by insults, such as ischemia, hypoxia, and trauma, frequently generate spreading depolarization (SD). At the neuronal level, SDs entail complete breakdown of ionic gradients, persisting for seconds to minutes. It is unclear whether these transient events have a more lasting influence on neuronal function. Here, we describe electrophysiological changes in cortical neurons after recovery from hypoxia-induced SD. When examined with standard measures of neuronal excitability sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 70 publications
(105 reference statements)
0
20
0
Order By: Relevance
“…Repeated episodes of cortical SD, hitherto unrecognized in brain tumor models, were captured; their potential proinflammatory effect adds a pathogenic mechanism that may play an amplifying role in progressive hyperexcitability. These pathological waves involve massive intracellular calcium influx mediated in part by NMDA receptor activation that transiently silences neuronal activity and briefly impairs the precise coding of high-frequency synaptic inputs in recovering neurons (55). SD appearance in brain tumors is of clinical relevance and may contribute to common transient neurological symptoms including confusional spells, motor deficits, and headache in glioma patients (56).…”
Section: Discussionmentioning
confidence: 99%
“…Repeated episodes of cortical SD, hitherto unrecognized in brain tumor models, were captured; their potential proinflammatory effect adds a pathogenic mechanism that may play an amplifying role in progressive hyperexcitability. These pathological waves involve massive intracellular calcium influx mediated in part by NMDA receptor activation that transiently silences neuronal activity and briefly impairs the precise coding of high-frequency synaptic inputs in recovering neurons (55). SD appearance in brain tumors is of clinical relevance and may contribute to common transient neurological symptoms including confusional spells, motor deficits, and headache in glioma patients (56).…”
Section: Discussionmentioning
confidence: 99%
“…The A152T-variant was also suggested to modulate the power of brain oscillations in the 0.5-6Hz frequency range, with suppression of hTau-A152T expression and levetiracetam treatment reported to reverse tau-dependent network dysfunction (Das et al, 2018), although, in this context, it is interesting to note that seizure-like low frequency activity may be naturally linked to cellular hypoactivity in the network, with a recent report of a similar effect resulting from hypoxia-induced spreading depolarization (Revah et al, 2019). Lastly, it is important to emphasize that two recent human studies have independently reported an association between measures of tau pathology and increased hippocampal activity during task-related fMRI in clinically normal older subjects (Berron et al, 2019;Huijbers et al, 2019).…”
Section: Taumentioning
confidence: 99%
“…Indeed, computational modeling work has revealed that emergent features of circuit dynamics are not simply related to cellular excitability thresholds or average synaptic strengths, but depend on subtle features of the neuronal populations' physiology, e.g. their speed and bandwidth (Brunel and Hakim, 1999;Geisler et al, 2005;Lazarov et al, 2018;Revah et al, 2019;Wei and Wolf, 2011), and critically on the speed of feedback inhibition Wolf, 2010, 2012;van Vreeswijk and Sompolinsky, 1996;Wolf et al, 2014). In addition, microcircuit models predict that relatively small differences in the overall strength of local circuit motifs can strongly affect computational function.…”
Section: Towards An Improved Theoretical Framework Of Circuit-level Changes In Admentioning
confidence: 99%
“…Increased firing may result from the reduction of inhibition (Elzoheiry et al, 2019), increased excitability (Fan et al, 2008), and ischemic long-term potentiation (Maggio et al, 2015). On the other hand, factors like the lack of energy-producing metabolites following hypoxia (Kass and Lipton, 1989), perturbed neuronal ion homeostasis (Müller and Somjen, 2000), and calciumtriggered disruption of the axon-initial segment morphology (Revah et al, 2019) may reduce neuronal activity following OGD and HSD.…”
Section: Discussionmentioning
confidence: 99%
“…This event results from the complete breakdown of the membrane potential due to insufficient ATP-driven pump activity and entails a dramatic shift of ions, including a massive influx of calcium. Interestingly, neurons recover their membrane potential and ability to fire action potentials upon timely re-oxygenation (Müller and Somjen, 2000;Hefter et al, 2016;Revah et al, 2019). It is suspected that HSD represents an additional insult, and it can be seen as a hallmark of HI-induced neuronal damage (Dreier, 2011).…”
Section: Introductionmentioning
confidence: 99%